GAMBARAN TINGKAT KECEMASAN ORANG TUA TERHADAP HOSPITALISASI ANAK DENGAN KEJANG DEMAM SELAMA ANAK DI RAWAT DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2017 - Melky Rismando Damanik; Rusmauli Lumban Gaol (Elisabeth Health Jurnal, 2017)
Anxiety is an unclear and widespread concern, associated with feelings of uncertainty and helplessness. This state of anxiety and emotion has no specific object but can affect behavior toward parents whose children are hospitalized. Parental anxiety levels are subjective experiences of the individual and can not be directly observed but consequently will affect the anxiety level of the parent. Hospitalization of children is a state of crisis in children, when children are sick and hospitalized, one of them in the febrile seizure disease is a seizure spasm that occurs in the rise in body temperature above 38 ° C this will result in anxiety level of parents increases. Goals: To know the description of anxiety level of parent to hospitalization of child with febrile seizure during child is treated in hospital of Elisabeth Elisabeth Medan. Method: The design used in this study is descriptive to describe the level of anxiety parents to hospitalization of children with febrile seizures during child care at Hospital Santa Elisabeth Medan Year 2017. Result: based on data collection found 10 respondents where 5 (50%) of respondents who experienced anxiety level in medium category and 5 (50%) respondents have low level anxiety level. Conclusion: Based on the research and data analysis that has been done in accordance with the objectives that have been determined can be concluded that all parents who care for their children in the hospital will experience anxiety level that is 5 respondents (50%) with moderate anxiety level, while 5 others (50% Low anxiety levels and high anxiety levels were not found.